It seems the text is unclear or contains accidental characters. Please rewrite or clarify your request so I can translate it into English. - Abbes , Asma (El Omda in Linguistics and Discourse Analysis, 2023)
The aim of this study is to measure the effect of prior knowledge on the understanding of the scientific text for a 10-year-old child, through an experience represented in reading a text on “climate” by a sample of 20 students. The results show that students who had a high level of prior knowledge on the subject of the text were able to achieve the third level of comprehension through mental representation of the text, while students who had a low level of knowledge were limited. only at local level